A Biochemical and Histochemical Study on the Activity of Acid Peptide Hydrolase in the Hypothalamus at Some Periods of Starvation and Refeeding after Starvation - Temur, Atilla; Karadag, Huseyin; Askerov, Fahrettin; Huseyin Donmez, H. (Asian Journal of Chemistry, 2016)
This study was carried out to determine acid peptide hydrolyse activity in the homogenate of the lateral (feeding centre) and ventro-medial (satiety centre) nuclei of hypothalamus and fractions of the cells (mitochondria, nucleus, cystocoele) in those centres of rats fed after being starved for a five day period. One hundred and sixty Wistar Albino rats were used in this study. The rats were starved for periods of 1, 3, 5 and 7 d. The rats starved for 5 d were then allowed to eat for periods of 5, 15 and 30 d. The activity of acid peptide hydrolyse was biochemically determined in the feeding and satiety centres. In addition, histochemical study was also done in these centres. It was observed that the activity of acid peptide hydrolyse became closer to the levels of the control group in the satiety centre on the 30th d of access to food after a 5 d starvation. It was concluded that the feeding centre was more sensitive to starvation than the satiety centre and the satiety centre was restored faster than the feeding centre.